Proceedings of the 18th LACCEI International Multi-Conference for Engineering, Education, and Technology: Engineering, Integrat 2020
DOI: 10.18687/laccei2020.1.1.322
|View full text |Cite
|
Sign up to set email alerts
|

Modelo combinado de SLP y TPM para la mejora de la eficiencia de producción en una MYPE del sector textil confecciones peruano

Abstract: The textile and clothing sector is one of the most important sectors in the Peruvian economy. Denim or also called Jean is one of the most representative and consumed products. A key factor for a denim garment to be accepted in the market is the quality regarding the hardness, resistance and pigmentation of the garment, characteristics that are developed in the washing and dyeing process, which makes this process of great importance in the elaboration of this garment. Most of the companies in this area have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…By validating the proposed model through simulation in the Arena software, the company is expected to reduce its production cycle time by 99.76 minutes, or 1.50 hours, due to the expected improvement in OEE by 13.88%, which means that the knitting machines would go from having a regular score of 69% to having an acceptable score of 82.88%. This result is related to other success cases, such as the case of a MSE in the textile and clothing sector in Peru, which, by implementing the TPM tool, increased its OEE by 16.17% and production efficiency by 5.12% (Quispe et al 2020). The same situation happened in a company dedicated to the manufacturing of clothing, which increased its OEE from 56% to 84% (Mejia and Rau 2019).…”
Section: Validationmentioning
confidence: 68%
See 1 more Smart Citation
“…By validating the proposed model through simulation in the Arena software, the company is expected to reduce its production cycle time by 99.76 minutes, or 1.50 hours, due to the expected improvement in OEE by 13.88%, which means that the knitting machines would go from having a regular score of 69% to having an acceptable score of 82.88%. This result is related to other success cases, such as the case of a MSE in the textile and clothing sector in Peru, which, by implementing the TPM tool, increased its OEE by 16.17% and production efficiency by 5.12% (Quispe et al 2020). The same situation happened in a company dedicated to the manufacturing of clothing, which increased its OEE from 56% to 84% (Mejia and Rau 2019).…”
Section: Validationmentioning
confidence: 68%
“…For example, a Peruvian Small and Medium-sized Enterprise (SME) demonstrated through the implementation of the TPM program that it was able to improve its OEE from 32.86% to 85.58% (Canahua 2021). Additionally, through research carried out in a MSE of the Peruvian textile and clothing sector, it was shown that through the implementation of the TPM program, the OEE of the company's machines improved by 16.17%, going from 68.21% to 84.38%, which solved its problem of low production efficiency in the washing and dyeing process (Quispe et al 2020). Likewise, an industrial company reduced the number of machine failures by 23% by carrying out preventive and corrective maintenance activities, which generated an increase in machine availability and OEE by 5% (Pinto et al 2020).…”
Section: Total Productive Maintenance (Tpm)mentioning
confidence: 93%
“…Low efficiency has a notable presence in the bulk of the MSEs in the textile-apparel sector in the country, due to factors such as the negative effects of Covid 19 [34], time of leisure, among others. Other researchers point out: "the production efficiency at the national level in Peru in this sector is on average 75.2%, while globally it is on average 80%, so we can deduce that Peru is below average" [35].…”
Section: A Initial Diagnosticmentioning
confidence: 87%
“…In addition, in [4] it is mentioned that many companies have a terrible use of physical space, excessive movement and unnecessary transport within the production plant. Therefore, it is of the utmost importance to solve the problem that most textile microenterprises are going through a model of improving productive efficiency in order to compete in the international market and increase the economy of the sector [7].…”
Section: A Model To Improve Operational Efficiencymentioning
confidence: 99%
“…A case study was selected that shows the problem due to the high generation of unproductive times due to not having established procedures, machine failures and stops, high preparation times in the process and unnecessary movements, which generate monetary losses equivalent to 29.19% of the annual gross margin of the case study. It is worth mentioning that, in various parts of the world, techniques have been developed for the solution of low efficiency in companies in the textile sector or other areas with similar problems, and usually focus on a single factor, which may be the machine or the operator [7]. However, if you want to optimize a process its necessary to consider an integrated approach that takes a joint view of the two factors, machines and operators.…”
Section: Introductionmentioning
confidence: 99%